The CSR of MNC Subsidiaries in Developing Countries: Global, Local, Substantive or Diluted? - Jamali, D. (Journal of business ethics, 2010)
With the advent of globalization, the track record of multinational corporations (MNCs) has been mixed at best in relation to their Corporate Social Responsibility (CSR) involvement in developing countries. This article attempts to cross-fertilize insights from the business-society and international business political behavior literature streams to identify relevant dimensions and contingencies that can be used to analyze the CSR of MNCs in developing countries and the extent of standardization or localization of their strategies. The article makes use of the new theoretical framework in the context of an interpretive research methodology to examine the CSR orientations of a sample of MNC subsidiaries in Lebanon. The findings reveal patterns of global CSR being diffused to developing countries, but also being diluted along the way in view of specific subsidiary endowments and host market characteristics.